On the relevance of exports for regional output growth in China - Christian Dreger; Yanqun Zhang (European University Viadrina, Department of Business Administration and Economics, 2013)
Despite high economic growth during the last decades, China is still vulnerable to shocks arising from industrial states. The advanced economies determine Chinese export performance, with subsequent effects on output growth. Using a production function approach, this paper examines to which extent regional GDP growth in China is export driven. In a panel of 28 Chinese provinces, series are splitted into common and idiosyncratic components, the latter being stationary. The results indicate cointegration between the common components of GDP, the capital stock and exports. In equilibrium, exports increase GDP by more than their impact expected from the national accounts. While exports and capital are weakly exogenous, GDP responds to deviations from the long run. An adjustment pattern can be detected for almost all regions, except of some provinces in the Western part of the country.
Keywords: F43; O11; C23; 330; Chinese economy; panel cointegration; export led growth